Permeability of the Treated Peat Soil Mixtures with Pond Ash – Hydrated Lime - Md. Yusof, Zeety; Mohamed, Kamaruzzaman; Bagus Mohamed Jais3, Ismacahyadi (International Journal of Engineering and Technology, 2019)
Peat soil has been identified as a Geotechnical engineering problem in the construction works because of its difficulties to predict it’s Geotechnical behaviour due to its volume instability. The aim of this paper was to analyse the permeability of the treated peat soil’s mix with the various percentages of pond ash (PA) (5, 10, 15 & 20%) and constant hydrated lime’s (HL) (12%) composition. The role of using PA and HL is to act as the reactant and accelerator in treating peat soil. The treated soil properties are great importance of the vital as the design contributes to the improvement of the peat soil. Therefore, this study investigated the significant evidence on the effect of untreated and treated peat soil from the laboratory works testing. The results of this study show that by increasing PA content from 5 to 20%, the admixtures were able to reduce the coefficient of vertical permeability of the treated peat soil in soaking time compared with the untreated peat soils. It is a significant evidence of the positive effects composition of the treated peat soil was discovered during the laboratory works.